Systematic Review of Education Quality Assurance Management in Schools Method Matching - AFRIADI, BAMBANG; Fatkar, Budiastuti; Mirza, Mochammad; Fitri, Fitri; Nur, Muhamad; Sobirov, Bobur; Colega Oli, Mario; Rosmeri Simorangkir, Melda Rumia; Isnaniah, Isnaniah; Prastowo, Sugeng Lubar (International Education Trend Issues, 2023)
Internal quality assurance in schools is essential because it pertains to a school's confidence in complying to national education standards and achieving a nation's national education goals. In the discussion of this study, it is crucial to determine the degree to which Education Quality Assurance in primary schools is based on comparable research findings. The approach used to evaluate several learning outcomes is the matching evaluation strategy. In addition, the utilised systematic review is a Narrative systematic review, which carefully picks and conducts with discretion what the researcher has written about a subject or problem. As a consequence of the study's results, it was established that the education system and schools are responsible for ensuring that all students meet the criteria and using their resources effectively and efficiently. Especially elementary school, which is the foundation of education. Academic Quality Assurance is essential for attaining academic quality (teaching and learning procedures and curriculum) and structural provision (buildings and physical facilities) in accordance with predefined objectives and standards.